Emotional Intelligence and Employee Turnover in the Hospitality Industry: Evidence from an Embedded Mixed-Methods Study in Naga City, Philippines - Angelica R. Buensalida; Chique G. Lizardo; Faith Nicole Olores; Ma. Cecilia P. Verdad; Annie Mae L. Buensalida; Christian Borromeo; Nico Ogarte (The Indonesian Institute of Science and Technology Research, 2026)
Employee turnover remains a persistent challenge in the hospitality industry due to high emotional demands, workload pressures, and continuous interpersonal interactions. This study investigates the influence of emotional intelligence (EI) on employee turnover among hospitality professionals in Naga City, Philippines. Specifically, it examines employees’ demographic profiles, levels of emotional intelligence, turnover motivations, and the relationships among these variables. An embedded mixed-methods research design was employed, involving 180 resigned employees from accommodation, food and beverage, and resort sectors. Quantitative data were analyzed using descriptive and inferential statistics, including weighted mean, Spearman’s rank correlation, and chi-square tests, while qualitative responses were analyzed through thematic analysis to enrich interpretation. The findings reveal that employees generally exhibit high levels of emotional intelligence, particularly in social skills and motivation. However, self-regulation emerged as the weakest dimension, indicating challenges in managing emotions under stress. Organizational factors such as workload, compensation, career growth limitations, and work-life imbalance were identified as moderately high contributors to turnover. The results further indicate that emotional intelligence significantly influences turnover motivations, although it does not independently prevent turnover in the presence of unfavorable working conditions. This study contributes to the literature by integrating emotional and organizational perspectives in explaining turnover behavior. It proposes a comprehensive retention approach through the CARE Program, emphasizing emotional intelligence development, managerial support, and employee well-being. The findings provide practical insights for hospitality organizations seeking to enhance employee retention and organizational sustainability.